Unexplained Wealth and the Reverse Burden of Proof: A Tool for Combating Public Sector Corruption - Undang Prasetya Umara; Amiludin Amiludin; Dwi Nurfauziah Ahmad; Kenjiro Ken Arwin (Jurnal Hukum Replik, 2025)
Public sector corruption remains a persistent challenge in Indonesia, undermining governance, public trust, and sustainable development. Conventional criminal justice approaches, which place the burden of proof solely on prosecutors, often prove inadequate in addressing complex corruption schemes characterized by concealed assets and illicit enrichment. This article examines the concept of unexplained wealth and the application of a reverse burden of proof as a legal mechanism for combating corruption within Indonesia’s public sector. Using normative legal analysis supported by comparative and doctrinal approaches, the study evaluates the compatibility of unexplained wealth frameworks with Indonesia’s constitutional principles, anti-corruption laws, and international obligations, particularly the United Nations Convention against Corruption (UNCAC). The findings demonstrate that a carefully designed reverse burden of proof, limited to asset recovery proceedings and accompanied by strong procedural safeguards, can enhance the effectiveness of corruption control without violating fundamental rights. The article contributes to the existing literature by offering a contextualized legal model for integrating unexplained wealth provisions into Indonesia’s anti-corruption regime, bridging the gap between global best practices and domestic legal constraints. It further provides policy-relevant insights for legislators and law enforcement authorities seeking innovative yet constitutionally sound tools to address illicit enrichment among public officials.